İş ağı ve uluslararasılaşma performansı arasındaki ilişkiye riskli yatırım yapma niyeti ve uluslararası fırsat tanımanın düzenleyici etkisi - Platin, Nida (My University, 2023)
Bu araştırmada, iş ağı ve uluslararsılaşma performansı arasındaki ilişkiye riskli yatırım yapma niyeti ve uluslarası fırsat tanıma kavramlarını düzenleyici etkilerinin incelenmesi amaçlanmaktadır. Araştırmanın evreni, Türk mobilya sektöründe üretim ve ihracat yapan ve aynı zamanda bir iş ağına dahil olan Kobiler oluşturmaktadır. Veriler anket yöntemi kullanılarak toplanmış, araştırmanın amacına uygun olarak oluşturulan araştırma modeli ve hipotezleri nicel tekniklerle analiz edilmiştir. Bulgularına göre araştırmanın literatüre ilk katkısı iş ağı ve uluslararasılaşma performansı arasındaki ilişkisinde iş ağının bağın gücü alt faktörünün öne çıkması olmuştur. Literatüre ikinci katkı uluslararası fırsat tanıma düzenleyici etkisi devreye girdiğinde ağın yapısı alt boyutu etkisinin öne çıkmış olmasıdır. Özellikle Uluslararası fırsat tanımanın alt boyutu olan ve fırsatların bilinçli,sistematik bir şekilde araştırılarak elde edilmesine anlamına gelen aktif uluslarası fırsat tanıma boyutunun iş ağının ağın yapısı alt boyutunu daha fazla öne çıkardığını söylemek mümkündür.

In this research, it is aimed to examine the regulatory effects of risky investment intention and international opportunity recognition on the relationship between business network and internationalization performance. The universe of the research consists of SMEs that produce and export in the Turkish furniture industry and who are also included in a business network. The data were collected using the questionnaire method, and the research model and hypotheses created in accordance with the purpose of the research were analyzed with quantitative techniques. According to the findings, the first contribution of the research to the literature was the prominence of the strength of tie as the sub-factor of business network, in the relationship between business network and internationalization performance. The second contribution to the literature is that the effect of the network structure sub-dimension came to the forefront when the international opportunity recognition regulatory effect came into play. In particular, it is possible to say that the active international opportunity recognition dimension, which is the sub-dimension of international opportunity recognition and means the conscious and systematic research of opportunities, highlights the network structure sub-dimension of the business network more.
The moderator effect of risky investment intentıon and international opportunity recognition on the relationship between business network and internationalization performance
Keywords: Finance; International business enterprises; International opportunity recognition; Internationalization performance; Investments; İş ağı; Kobi Business network; Maliye; Risk management; Risk yönetimi; Riskli yatırım yapma niyeti; Risky investment intention; SMEs; Uluslararası fırsat tanıma; Uluslararası ticari teşebbüsler; Uluslararasılaşma performansı; Yatırımlar